Die Mittelschicht in Deutschland: Vielschichtig und stabil; The middle class in Germany: Diverse and stable - Judith Niehues (IW-Trends - Vierteljahresschrift zur empirischen Wirtschaftsforschung, 2017)
Die Mittelschicht steht häufig im Zentrum von Verteilungsanalysen. Es besteht allerdings keine eindeutige Abgrenzung dieser Einkommensgruppe. Zudem gibt es unterschiedliche Befunde hinsichtlich ihrer langfristigen Entwicklung. Gemäß der Abgrenzung des Instituts der deutschen Wirtschaft Köln (IW Köln) gehörte ein Alleinlebender im Jahr 2014 zur (Einkommens-)Mittelschicht im engen Sinn, wenn er über ein monatliches Nettoeinkommen zwischen 1.410 und 2.640 Euro verfügte. Für eine vierköpfige Familie liegen die Einkommensgrenzen bei 2.950 und 5.540 Euro. Unabhängig von der Abgrenzung stellt die Einkommensmittelschicht die mit Abstand größte Bevölkerungsgruppe in Deutschland. Auf Basis aktueller Daten der SOEP-Welle 2015 und der Definition des IW Köln gehört ihr etwa jeder Zweite an. Dies hat sich seit der Wiedervereinigung nicht wesentlich geändert. Die Entwicklung seit 1991 kann in drei Phasen eingeteilt werden: Zunächst stieg der Anteil der Mittelschicht im Zuge des ostdeutschen Aufholprozesses etwas an, bevor er von seinem temporären Höchstpunkt von knapp 55 Prozent im Jahr 1997 auf rund 50 Prozent bis 2005 zurückging. Abgesehen von dem Einfluss einer Stichprobenänderung im Jahr 2013 hat sich das Schichtgefüge seither nur noch unwesentlich verändert. Die Mittelschicht in Deutschland ist stabil. – – Although the middle class is frequently at the centre of distribution analyses, there is no precise definition of this income group. Findings as to its long-term development have, moreover, varied. As defined by the Cologne Institute for Economic Research (IW), a person living alone in 2014 was considered middle class in the narrow sense of the word if he or she had a monthly net disposable income between 1,410 and 2,640 euros. For a family of four the income limits were 2,950 and 5,540 euros. However defined, the middle class as an income group represents by far the largest section of the population in Germany. Based on current data from the 2015 wave of the Socio-Economic Panel (SOEP) and applying the IW definition, approximately every second person is a member of the middle class, a figure which has not changed fundamentally since German reunification. Developments since 1991 can be divided into three phases. First the middle class grew slightly as a proportion of the total population as the formerly communist east of the country caught up economically. From a peak of almost 55 per cent in 1997 it then declined to around 50 per cent in 2005. Apart from the influence of a change in the sampling procedure in 2013 the country's class structure has changed but little since then. There is certainly no evidence of the middle class continuously eroding at the edges. The present analysis reveals that the boundary between the middle and lower classes does not run along the so-called 'collar line'. Skilled blue-collar workers are highly likely to belong to the narrowly-defined middle class, as are trained white-collar workers. The self-employed, civil servants at management level and white-collar workers in highly-skilled or managerial positions frequently qualify as at least upper middle class and thus belong to the richest quintile of society.
Keywords: D31; D63; I31; 330; Mittelschicht; Einkommensverteilung; Schichtzusammensetzung